Global Incidence of Sporadic Vestibular Schwannoma: A Systematic Review. (31st August 2021) - Marinelli, John P.; Beeler, Cynthia J.; Carlson, Matthew L.; Caye‐Thomasen, Per; Spear, Samuel A.; Erbele, Isaac D.
Abstract : Objective: Ubiquitous throughout the literature and during patient counseling, vestibular schwannoma is often quoted to affect about 1 per 100, 000 people. Yet, reports from distinct international populations suggest that the incidence is likely much higher. The objective of the current work was to systematically characterize the global incidence of sporadic vestibular schwannoma. Data Sources: Scopus, Embase, and PubMed. Review Methods: Population‐based studies reporting incidence rates of sporadic vestibular schwannoma between January 2010 and August 2020 were searched with language restrictions requiring reports to be published in Chinese, English, German, Italian, or Spanish. The protocol was registered with PROSPERO (CRD42021228208) prior to commencement of data collection. PRISMA guidelines for transparent reporting of systematic reviews were followed. Results: Among 424 citations, 6 publications covering 4 distinct populations from Denmark, the Netherlands, Taiwan, and the United States met inclusion criteria. Most recent incidence rates of among all ages ranged between 3.0 and 5.2 per 100, 000 person‐years. Highest incidence rates were reported among patients aged ≥70 years, peaking at 20.6 per 100, 000 person‐years. One study from the United States reported the incidence of asymptomatic, incidentally diagnosed tumors at a rate of 1.3 per 100, 000 person‐years from 2012 to 2016. Conclusions: Recent international incidence rates of sporadic vestibular schwannoma exceed the commonly quoted "1 per 100, 000" figure by up to 5‐fold among all ages and by up to 20‐fold among age groups at highest risk. Based on modern incidence rates, the lifetime prevalence of developing sporadic vestibular schwannoma likely exceeds 1 per 500 persons.